State and Devolution: Economic Crises and the Devolution of U.S. Superstate Power - Schaeffer, Robert (The International Journal of Sociology of Agriculture and Food, 2021)
This paper examines the incorporation of superstate power by U.S. state organizations after World War Two and the subsequent ’devolution’ or transfer of U.S. authority to superstate organizations in response to contemporary economic crisis. After analyzing the crises that let to the devolution of U.S. agricultural and monetary authority, the paper discusses the implication of these developments for a theory of states in the interstate system, arguing that the seizure of state power may no longer be a useful or relevant objective for social movements.